A Synaptic Transistor Based on Monolayer Monocrystalline‐MoS2 for Neuromorphic Applications. Issue 8 (1st June 2021) - Yan, Meng; Hu, Kai; Wang, Fang; Shan, Xin; Lin, Xin; Chen, Peng; Zhao, Xuanyu; Wei, Junqing; Song, Zhitang; Zhang, Kailiang
Abstract : Ultrathin 2D semiconductor materials have attracted tremendous attention due to their potential application in neuromorphic computing, especially for electronic devices with high stability and low energy consumption. Two‐terminal memristors cannot extend the range of functionalities for complex neuromorphic applications due to their inherent single presynaptic input; thus three‐terminal synaptic transistors based on monolayer monocrystalline‐MoS2 films grown by chemical vapor deposition (CVD) are fabricated in this work. Importantly, there are two modes including drain and gate dual tunability available in nonvolatile memory functions. Both drain terminal and gate terminal can be used as presynaptic inputs to successfully simulate excitatory/inhibitory postsynaptic current (EPSC/IPSC), spike‐amplitude‐dependent plasticity (SADP), spike‐timing‐dependent plasticity (STDP), and long‐term plasticity (LTP) of biological synapses, providing multiple degrees of freedom for synaptic weight modulation. The conductance modulation of drain and gate terminals can be attributed to the migration and charges trapping/detrapping process of sulfur vacancies. Using monocrystalline‐MoS2 films, the device not only attains a lower operation voltage and a higher endurance (5000 cycles), but exhibit low energy consumption during the LTP process (≈3.75 pJ) with the gate terminal, indicating more flexibility and great potential of complex neuromorphic application. Abstract : Three‐terminal synaptic transistors provide two modes where both the drain terminal and the gate terminal can be used as presynaptic inputs to simulate synaptic behaviors. Devices based on monolayer monocrystalline‐MoS2 films are reported, which not only attain a much lower operation voltage and a higher endurance, but exhibit low energy consumption during the LTP process with the gate terminal, indicating great potential for complex neuromorphic applications.